Value trees usefulness in assessment of enterprise architectures value - Rodrigues, Luis Silva (2010)
In last two decades a significant number of organizations began to build Enterprise Architectures in order to deal with complexity and change, to align business and IT, to cut costs and several other objectives. The current economic pressures and the significant investment that Enterprise Architectures represents are increasingly demanding an assessment and demonstration of their usefulness and value. Despite the need and interest there still is no consensus on how to demonstrate the value. Some value models and methods have already been presented but they are still not detailed enough to be used and require further research to be useful for most organizations. In this paper, we present an initial discussion about the usefulness of value drivers and value trees as a way to measure the Enterprise Architectures value.